2009
DOI: 10.1002/jmv.21416
|View full text |Cite
|
Sign up to set email alerts
|

High‐risk HPV types in lesions of the uterine cervix of female commercial sex workers in the Philippines

Abstract: In order to prevent cervical cancer, vaccines against human papilloma virus types 16 (HPV-16) and 18 (HPV-18) have been implemented worldwide. However, the HPV types that cause cancer can differ according to geographical area and ethnicity. In this new era of the HPV vaccine, it is important to elucidate the prevalent HPV types in each area. Therefore, the prevalence of HPV infection and cervical abnormalities among 369 female commercial sex workers in the Philippines were examined. HPV L1 gene was amplified b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 41 publications
5
36
1
1
Order By: Relevance
“…The prevalence of HPV infection in female CSWs from other countries was 57% in the Philippines [11], 39% in Spain [12], 32% in Australia [13] and 48% in Japan [14]. In our previous data [15], the prevalence of HPV infection in high-risk women was 47% with the Hybrid Capture II method (Digene Diagnostics).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of HPV infection in female CSWs from other countries was 57% in the Philippines [11], 39% in Spain [12], 32% in Australia [13] and 48% in Japan [14]. In our previous data [15], the prevalence of HPV infection in high-risk women was 47% with the Hybrid Capture II method (Digene Diagnostics).…”
Section: Resultsmentioning
confidence: 99%
“…[16], the prevalence of HPV infection for female university students in Busan was 15.2% and the common HPV genotypes were HPV-51, -53, -56, -16 and -52. In CSWs in the Philippines, HPV-52 was the most prevalent genotype and other dominant types were HPV-66, -16, -45 and -67 [11]. Among general gynecology practices in South Taiwan, the prevalent genotypes were HPV-16, -52, -58, -18 and -51 [19].…”
Section: Resultsmentioning
confidence: 99%
“…In all studies the majority of FSWs were less than 20 years old at the age of sexual initiation: Africa 16.7 years old [16]; Americas 9-22 years [18, 27]; Europe: 16 years [24]; and in the Western Pacific 15-20 years of age [15, 23, 28]. Eastern Mediterranean regions did not give a specific age but indicated that a majority were less than 20 years old [19].…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of cervical HPV is comparable to that observed in FSW in Japan (48%)[31], Korea (47%)[23], Tunisia 43.8%[32], Senegal (43%)[33], and Bulgaria (43.4%)[34], but somewhat lower than other locales including Vietnam (85%)[6], Kenya (55.6%)[35], Peru 65.8%[36] and the Philippines (57.2%)[9]. The mean age of FSW in these studies ranged from 24–31 years old, similar to our study (mean 26 years old).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies have reported that the prevalence of single or multiple HPV infections and HPV viral load was higher among women infected with HIV [19,21,22]. Women engaged in sex work have multiple sex partners, and are consequently at higher risk of both HIV and HPV infection [6,9,23,24]. Understanding the determinants of cervical HPV infection is an essential step in developing effective interventions for the prevention of infection, and ultimately cervical cancer.…”
Section: Introductionmentioning
confidence: 99%